Evaluation of external noise produced by transverse rumble strips on rural roadways - Othman, Mohd Hanifi; Haron, Zaiton; Mohd Yusof, Mohd Badruddin; Hainin, Mohd Rosli; Yahya, Khairulzan; Yaacob, Haryati; Azman, Shamila (Trans Tech Publications, 2012)
Transverse rumble strips (TRS) are widely used by local authority in Malaysia to reduce vehicle speed and alert drivers to any changes on the road. The objective of this study was to evaluate the anticipated community reaction due to the external noise produced by the TRS. The evaluations were carried out through the noise levels measurement, calculation of the TNI and anticipated community response analysis. Measurements of noise level were taken at two locations of a rural roadway that have received complaints from the public i.e Kampung Pengkalan Raja (KPR) and Kilometer 52 (KM52) of Johor Bahru-Pontian federal road, in Pontian District, Johor. Results showed that TRS can increase the level of traffic noise, TNI values, and annoyance response in community. TNI values of 126dB(A) and 119dB(A) for KPR and KM52, respectively were exceeded suggested level of TNI for planning purpose of 74 dB (A) for 3% annoyance from the social surveys. Anticipated annoyance response analysis also indicated that resident in both locations received strong to very strong impact that can lead to vigorous community reaction and this was in agreement with the real reaction from the community.